MATRIARCHY: DISTORTION OF THE CONCEPT OF EMANCIPATION IN THE HOUSEHOLD AND ITS IMPACT ON SOCIAL WELFARE - Ginting, Rika Githamala; Rizki, Cici Indah (Journal Analytica Islamica, 2025)
Emancipation is often associated with the feminist movement to fight for women's rights and rejection of discrimination. Enforcement of emancipation is marked by the movement of women to erode patriarchy. Over time, the concept of emancipation underwent a shift in meaning, giving birth to a radical new understanding. This understanding is matriarchy, namely the extreme domination of women and the desire of women's groups to dominate other people in terms of thoughts, ideas, and even the life processes of other groups so that they accept their ideas. What's worse is that this matriarchal understanding is absorbed and applied in households which is very contrary to Islamic provisions. The analytical method used is descriptive qualitative analysis with a conceptual approach and a case approach. The results of the study indicate that there is a distortion regarding the concept of emancipation in the household, which creates matriarchy. The concept of matriarchy itself is not in line with Islamic teachings. The condition of matriarchy affects social welfare if in a family this understanding continues in the long term. As a result, there will be disputes that end in divorce so that social welfare cannot be felt in the family. The solution to overcoming this matriarchy is to understand each other's nature, and carry out the rights and obligations that have been ordained by God as well as possible.